Intelligent correlation method of typical business data in power communication operation management - Guilong WU; Zhimin YANG; Yu HUANG (Dianxin kexue)
In the process of power communication operation management, various independent business data, such as trouble tickets, duty logs, maintenance tickets, and inspection records, are generated and stored.These business data provide important support for the operation management of the power communication network.At present, the statistical process of most business data is relatively independent, and there is less manual correlation in the later stage.Two typical business data of duty log and trouble ticket in power communication operation management were selected, text mining technology was used to build a machine learning model combining unsupervised recall and supervised classification, and the intelligent association method between duty log and trouble ticket was proposed.Besides, the relevant historical business data in the electric power communication operation management system was used to do the experimental verification of the intelligent association method.The results show that it can achieve positive effect.